Lives given to freedom. Dictations to communist fighters. [Contribs of V.M. Goncharov (Gončarov), P.Y. Demchenko (Demčenko), S.I. Dorofeev a.o. Ed. by I.V. Milovanov and L.N. Chernov (Černov). Transl. by P.F. Kostyuk (Kostjuk) and S.V. Rosenberg (S.V. Rozenberg) (»Nauka", 1966)
USSR Academy of Sciences. Institute of Peoples of Asia, etc. Original title: Žizn', otdannaja bor'be. Rasskazy o kommunistach.